Large Basal Cell Carcinoma over Face reconstructed with rotational flap; an experience in a District level hospital - Shaheen Ahamed; Sadia Tun Marzia; Mausumi Iqbal (Update Dental College, 2015)
Basal cell carcinoma (BCC) is the most common form of skin cancer. BCC in the head and neck usually presents as a slow growing well defined papule or nodule located above the line connecting the angle of the mouth and ear lobe. It is locally destructive lesion and cause serious disfigurement but metastasizes rarely. Various treatment are available out of which surgical excision is the most standard option. Surgical excision of tumors from the face may create a defect that is difficult to restore. Skin grafts can only cover superficial defects and has a natural tendency to contract and may not take properly. Also, because of the color mismatch, it is not cosmetically identical to the face. The use of regional flaps such as rotational cheek flap can be a very good option for the reconstruction of a moderate to large cheek defect. Herein, we report a case of large BCC over the face for which rotational cheek flap reconstruction was carried out at Modernized Sadar Hospital, Chapainawabganj. Update Dent. Coll. j: 2015; 5 (1): 35-37